RANCANG BANGUN SISTEM INFORMASI BENGKEL UNTUK PENGELOLAAN TRANSAKSI DAN PENINGKATAN PELAYANAN KEPADA PELANGGAN - Rin Rin Meilani Salim (Jurnal Ilmiah Matrik, 2019)
Abstract : Bengkel is a business entity engaged in the sales and service of vehicle repair. The business process in the bengkel handles activities of purchasing, inventory, sales and service. In handling these activities, several problems were found, including frequent loss of purchase invoices, didn’t have debt due reports, inventory of goods not recorded properly, frequent errors in recording and calculating sales and service, not yet well-recorded technicians handling each repair from customers, and there are no purchasing reports to know purchase target achievement. Therefore, the bengkel needs an information system to manage daily transactions. The use of bengkel information systems will certainly improve service to customers because all activities and transactions are well managed by the bengkel information system. The information system developed has the advantage of being able to customize features according to needs and is flexible to be used by all bengkel